Radical Nephrectomy for Renal Cell Carcinoma in a Tertiary Care Hospital in Islamabad - Roman, Mohammad; Habib, Bilal; Anwar, khursheed (Pakistan Armed Forces Medical Journal, 2022)
Objective: to identify the demographic, laboratory, radiological and histological features of RCC patients presenting to a tertiary care hospital in Islamabad. Study Design: Cross-sectional study. Place and Duration of Study: Pakistan Atomic Energy Commission General Hospital, Islamabad Pakistan, from Jan 2014 to Aug 2021. Methodology: All the patients who underwent radical nephrectomy for histologically confirmed RCC at PAEC General Hospital Islamabad were included in the study. Demographic variables, ultrasound features, laboratory measures, histological types and Fuhrman grading were noted. Results: A total of 65 consecutive patients were included, which included 38(58.5%) males. The mean age of the patients was 52.6±8.6 years. The most common symptom was flank pain (42.2%). The diagnosis was made incidentally in 26 patients. The most common ultrasound feature was capsule involvement (23, 35.3%), and most cases were Fuhrman Grade-II (22, 48.9%). On histology, clear cell carcinoma was the most common RCC (40, 61.5%). Post-operative early RFT deterioration was noted in 32(49.2%) patients. This was significantly associated with greater tumour size, Fuhrman Grade-III/IV, renal vein thrombosis, gerota fascia, and ureteric involvement. There was no mortality in our study during the admission days until discharge. Conclusion: Renal cell carcinoma was more common among males and at a later stage of life (5th decade). The most common type was clear cell carcinoma. Post-operative early RFT deterioration was noted in 49.2% of patients. It was associated with greater tumour size, Fuhrman Grade III and IV, renal vein thrombosis, gerota fascia, and ureteric involvement.